’Awareness’ in metamorphosing pupae (Lepidoptera: Pieridae) - Hawes, Timothy C. (Fragmenta entomologica, 2019)
Neurobiological studies of model insect species have established that the nervous system retains some larval innervations, remodels others, and develops other new adult innervations during metamorphosis. Using a simple behavioral response – the ability to ‘kick’ by pupae of the pierid, Catopsilia pomona (Fabricius, 1775) - it was possible to assay for the retention of environmental awareness during ontogenetic reorganization. All pupae kicked 24h after ecdysis, 48% of pupae kicked at the pharate adult stage, and 28% of pupae kicked every day of their development (6.52 d ± 0.10). Both the mode and temporal expression of the response indicate that this retained awareness has larval origins. Variability in the response supports the inference that this response is mediated, to some extent, by prior experience rather than purely ‘reflex’. This is consistent with a Darwinian explanation of the behavior (and retained environmental awareness itself) as serving a protective function in pupae.